2018
DOI: 10.1177/2380084418794377
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Motivational Interviewing to Prevent Early Childhood Caries in Public Housing

Abstract: When viewed in light of the findings from the companion Pine Ridge study and other recent MI studies, the results of this study suggest that when the complex disease of early childhood caries is addressed in high-risk populations, MI is not effective, and alternative approaches are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(108 citation statements)
references
References 34 publications
1
107
0
Order By: Relevance
“…Similarly, personal approaches such as home visiting and telephone contacts can reduce ECC by increasing caregivers’ health literacy and self‐efficacy to change behaviours to improve their infants’ oral health . Knowledge increases, however, may not improve oral health behaviours or reduce caries increment …”
Section: Community Management Of Eccmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, personal approaches such as home visiting and telephone contacts can reduce ECC by increasing caregivers’ health literacy and self‐efficacy to change behaviours to improve their infants’ oral health . Knowledge increases, however, may not improve oral health behaviours or reduce caries increment …”
Section: Community Management Of Eccmentioning
confidence: 99%
“…Following the interviewing, the parent/caregiver may be asked to commit to self‐management goals that will be discussed at the child's subsequent appointment . Two randomized trials of motivational interviewing interventions to affect oral health behaviours and dental caries prevalence in low socioeconomic pre‐school children, however, have shown no effect on parents’ oral health behaviours or progression of ECC …”
Section: Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of individual approaches have been tested for the prevention of ECC, and studies using an approach based on motivational interviewing (MI) have shown that this is more effective than others in preventing the disease in some populations . On the other hand, two recent studies evaluating MI‐based interventions for populations at high risk for childhood caries found no reduction in caries, even improving mothers' oral health knowledge . However, the differential effect of MI on different social strata has not been evaluated in published studies.…”
Section: Introductionmentioning
confidence: 99%